Development of An Inquiry-Based Ethnochemistry Textbook To Improve Students' Scientific Literacy and Understanding - Hendrawani, Hendrawani; Hatimah, Husnul; Safitri, Baiq Rina Amalia; Pahriah, Pahriah (Universitas Pendidikan Mandalika, 2025)
This research aims to develop an ethnochemistry-based chemistry textbook with an inquiry approach to increase students' scientific literacy and understanding of chemical concepts. The research method used is Research and Development (R&D) with a 4D model (Define, Design, Develop, Disseminate). The textbook was tested on class X I students at MA Daru Muhyiddin NW Santong. The validation results show very good quality, with an average score of 4.75 from experts, 4.5 from practitioners, and 4.3 from students. This book is considered relevant to the curriculum, effective in increasing student understanding, and connecting chemistry with local culture. Suggestions for development include adding a glossary, visualization, and variations in inquiry activities. This book has great potential as an innovative learning medium based on local culture.